Illness according to the manugbulong (folk healers) of Igbaras and Miag-ao, Iloilo - Aquino, Mary Grace P.
This study explores and documents the different attributions of illness by manogbulong or folk healers of Miagao and Igbaras in the province of Iloilo. It contributes to the deepening of our understanding of indigenous conceptions of manogbulong and illness., Different practices indicate one or more specializations among the selected manogbulong, namely: surhuano, surhuana, manoghilot, manogluy-a, paltira, baylan and manogbot-bot. There are three different causes of illness according to the manogbulong. Unseen beings (like fairies, the elves, ghosts); persons with special powers (such as witches and socerers); and, physiological functions or injuries (like cramps, muscle pains, fatigue, kibit, bali or bone dislocation, etc.). The results of the study are as follows: First, sex (male/female) and type of locality (upland or coastal) of the manogbulong does not affect their perception of illness. Second, differences on perception of illness are associated with their specialization. For example, the surhuano/surhuana believed that unseen beings and people with special powers are always the cause of illness. The manoghilot on the other hand belived that hangin (cold air) is the primary cause of illness. When the hangin penetrates the ugat (blood vessels), an illnesses of physiological ailment occurs.